Spinal Cord Injury Without Radiological Abnormalities and the importance of Magnetic Resonance: not only diagnostic, but also predictive! - Martinez-Perez, Rafael; Joswig, Holger; Rayo, Natalia; Bertazzo-Silveira , Giuliano (Acta Biomedica Atenei Parmensis, 2020)
Comment on: Bonfanti L, Donelli V, Lunian M et al. Adult Spinal Cord Injury Without Radiographic Abnormality (SCIWORA). Two case reports and a narrative review. Acta Biomed 2018; 89: 593-598